The The Effect of Transcutaneous Electrical Nerve Stimulation in Low Back Pain: a Narrative Review - Karisa, Putri; Mutiara Annisa; Rositianti; Nita Fitria (International Journal of Nursing and Health Services (IJNHS), 2023)
Low back pain is a common musculoskeletal disorder that occurs in various parts of the world. Pain due to LBP causes a decrease in the quality of life and individual productivity. Pharmacological therapy that causes many side effects is felt, causing non-pharmacological therapeutic approaches to be needed, one of which is TENS, providing a positive effect with minimal side effects. This study aims to review the effect of TENS on pain due to LBP. The approach taken is a narrative review by identifying articles in PubMed, CINAHL, and Scopus from 2017-2022 using keywords: low back pain, TENS, pain level, chronic pain. As a result, five articles with RCT studies were included in the analysis. TENS showed a positive effect on reducing pain compared to other interventions, but it was temporary. Although TENS can be used for pain management of LBP, the evidence for its effectiveness is still being studied